2021
DOI: 10.1186/s12941-020-00410-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Streptococcus pneumoniae isolated from pediatric community-acquired pneumonia in pre-conjugate vaccine era in Western China

Abstract: Background Streptococcus pneumoniae (S. pneumoniae) is one of the most common pathogens which can cause morbidity and mortality in pediatric infections worldwide. This study aimed to describe the phenotypic and molecular characteristics of community-acquired pneumonia (CAP)-causing S. pneumoniae recovered from children in Western China. Methods We retrospectively enrolled pediatric patients younger than 5 years diagnosed with CAP. All 419 S. pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
(25 reference statements)
3
11
0
Order By: Relevance
“…It is well known that the distribution of S. pneumoniae serotypes changes over age, geographic region, time, and diseases [ 27 , 28 ]. In our study, the most frequent serotypes in CAP carriers group were 3, 19F, 19A, which were similar to other recent studies in China [ 16 , 29 ], however different with serotypes in Italy [ 30 ]. Additionally, the major serotypes from asymptomatic carriers were 3, 6, and 19F in our study, whereas were 19F, 6B, and 6C in Brazil [ 31 ], indicating that serotypes is closely related to geographic region.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is well known that the distribution of S. pneumoniae serotypes changes over age, geographic region, time, and diseases [ 27 , 28 ]. In our study, the most frequent serotypes in CAP carriers group were 3, 19F, 19A, which were similar to other recent studies in China [ 16 , 29 ], however different with serotypes in Italy [ 30 ]. Additionally, the major serotypes from asymptomatic carriers were 3, 6, and 19F in our study, whereas were 19F, 6B, and 6C in Brazil [ 31 ], indicating that serotypes is closely related to geographic region.…”
Section: Discussionsupporting
confidence: 91%
“…On the other side, we found that serotypes 3 and 19F were frequently found in both asymptomatic carriers and CAP carriers. Indeed, these serotypes are common in asymptomatic carriers and CAP carriers worldwide [ 16 , 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent epidemiological studies reported the predominant or common serotypes of S. pneumoniae isolates prevailing in the different areas and adjacent countries of China. 19F, 6B, 23F, and 19A were the common serotypes observed among the S. pneumoniae isolates in Western China, while 19F, 19A, and 23F were the predominant serotypes among the S. pneumoniae isolates in North China ( Zhao et al, 2020 ; Liang et al, 2021 ; Zhou et al, 2022 ). In the different areas of Southwest China, 19F and 19A were the predominant pneumococcal serotypes ( Shen et al, 2017 ; Ma et al, 2021 ; Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…However, β-lactam antibiotic resistance rates of S. pneumoniae isolates from different areas and countries have a large diversity. For example, PNC and CTX resistance rates among the S. pneumoniae isolates from Western China, North China, and Southwest China were 1.2–79.9% and 0.5–28.6% ( Shen et al, 2017 ; Zhao et al, 2020 ; Liang et al, 2021 ; Yan et al, 2021 ; Zhou et al, 2022 ), while the PNC resistance rates among the S. pneumoniae isolates from East Asia (Japan and South Korea), Southeast Asia (Thailand and Malaysia), India, United States, Europe, and Latin America were 1.7–22.8%, 4–83.1%, 10%, 10.8%, 19.4%, and 68.6%, respectively ( Mendes et al, 2016 ; Yahiaoui et al, 2016 ; Singh et al, 2017 ; Park et al, 2019 ; Moreno et al, 2020 ; Wangirapan et al, 2020 ; Dzaraly et al, 2021 ; Yanagihara et al, 2021 ). In this study, the PNC non-susceptible rate among the 309 S. pneumoniae isolates was as high as 81.6% (63.2% intermediate and 18.4% resistant), but the CTX non-susceptible rate was only 14.2% (11.6% intermediate and 2.6% resistant).…”
Section: Discussionmentioning
confidence: 99%